Structural and dynamic properties of IL1 receptors - Zhukova, J. V.; Lopatnikova, J. A.; Sennikov, S. V. (Frontiers in Immunology, 2025)
The study of the structural and dynamic properties of multidomain proteins is of great interest as they constitute one of the main regulatory mechanisms in the ligand–receptor system. The interleukin-1 (IL-1) family is a group of proinflammatory, pleiotropic cytokines whose activity is primarily mediated through two primary signaling receptors—the IL-1 type I receptor (IL-1R1) and the IL-1 receptor accessory protein (IL-1R3), which acts as a coreceptor—and a decoy receptor, the IL-1 type II receptor (IL-1R2). Their key ligands include the agonists IL-1α and IL-1β, and the endogenous antagonist IL-1 receptor antagonist (IL-1Ra). Evaluating the interdomain movements of these receptors is expected to shed light on the mechanisms of ligand binding and the development of a functional cellular response. Furthermore, analysis of the literature allows us to identify key aspects of the conformational dynamics of IL-1 receptors. It is established that the flexibility of the domains of these receptors plays a crucial role in their ability to adapt to various ligands and ensure accurate signal transmission in the cell. Analysis of the structural and functional features of these receptors allows us to determine the mechanisms underlying their interactions and identify differences in their functional activities. Understanding the structural mechanisms that give rise to domain flexibility can enable us to develop molecules which are capable of specifically modulating the activity of these receptors. This facet is especially important in the context of treating inflammatory and autoimmune diseases for the creation of new approaches to therapy.